Nickel-Catalyzed Oxidative Transamidation of Tertiary Aromatic Amines with N-Acylsaccharins - Liu, Shengzhang; Yang, Lingyun; Tao, Jiasi; Yu, Weijie; Wang, Tao; Fu, Junkai (Synlett, 2021)
The use of tertiary amines as surrogates for secondary amines has prominent advantages in terms of stabilization and ease of handling. A Ni-catalyzed transamidation of N-acylsaccharins with tertiary aromatic amines is reported. By using tert-butyl hydroperoxide as the terminal oxidant, this reaction permits selective cleavage of the C(sp3)–N bonds of unsymmetrical tertiary aromatic amines depending on the sizes of the alkyl substituents.
Keywords: transamidation; nickel catalysis; amides; tertiary amines; C–N bond cleavage